Pengaruh Pendidikan Kewirausahaan Terhadap Intensi Kewirausahaan, Karakteristik Wirausaha Sebagai Variabel Intervening - Nakulo, Koko; Asdani, Andi (STIE Malangkucecwara, 2016)
The purpose of research is to (1) determine the influence of entrepreneurship education to the level of entrepreneurial intentions; (2) to determine the influence of entrepreneurship education to the intention of entrepreneurship, entrepreneurial characteristics as an intervening variable. The population in this research were all students of Politeknik Negeri Malang. The sampling method using a non-probability sampling and sampling was done by using purposive sampling. Characteristics of the sample selection are students who have gained entrepreneurial education likes entrepreneurship courses and seminars or entrepreneurship training and entrepreneurship. Data analysis techniques which used in this research are analysis descriptive statistics and inferential statistical analysis, path analysis. The result known that entrepreneurship education has a significant influence directly to intense of entrepreneurship. Entrepreneurship education has indirect influence to intense entrepreneurship through characteristics of entrepreneurship variable. From the coefficient of determination has value 98.271% indicates that the variable of characteristics of the entrepreneur is a good mediator to improving the entrepreneurial intense